Future Direction of Language Education in Malaysia - Hajibah, Othman; Soubakeavathi, Rethinasamy (Penerbit Universiti Kebangsaan Malaysia, 2012)
Future Direction of Language Education in Malaysia starts by tracing the beginning of language education at tertiary level from the setting up of the Department of Languages in the Faculty of Arts at the University of Malaya in 1966 to the present. The rich past and present experiences are invaluable resources that can be used to chart the future direction of the national language education agenda to produce employable graduates both for the local and global workplaces in line with the objectives of the National Higher Education Strategic Plan (2007). This study compiles and examines a comprehensive database of language programmes pertaining to Languages, Linguistics and Literature offered in the different universities in the country to provide MOHE as well as the public with an overview of the discipline of language encompassing Malay (as the national language), English (as the country’s second language), and other languages. In doing so, the study highlights three main categories of language education in Malaysia i.e. language proficiency courses; language programmes; and programmes for teaching languages as a platform to understand where language programmes stand in the system.